2003
DOI: 10.1097/00042737-200303000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid stress in the mother and baby unit

Abstract: Intrahepatic cholestasis of pregnancy (ICP) affects about 0.7% of deliveries in Britain. It is regarded as a benign condition for the mother but is associated with increased fetal mortality in late pregnancy and early delivery is advised. Ursodeoxycholic acid (UDCA) treatment is beneficial to the mother and does not appear to harm the fetus. ICP is often regarded as a disease of the maternal liver already made 'cholestatic' by high levels of circulating progesterone. We propose that ICP should be considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…These compounds cross the placenta mostly in the fetomaternal direction. The impaired maternal clearance produced by ICP can limit the passage of BA from fetus to maternal circulation thereby inducing a further elevation of BA levels in the fetal circulation, 3,12,13 and high BA levels in the neonates could easily pass to the alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds cross the placenta mostly in the fetomaternal direction. The impaired maternal clearance produced by ICP can limit the passage of BA from fetus to maternal circulation thereby inducing a further elevation of BA levels in the fetal circulation, 3,12,13 and high BA levels in the neonates could easily pass to the alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…SULT2A1 sulfonates the gonadal hormone precursor DHEA and provides the starting material for estrogen biosynthesis in the placenta (Barker et al, 1994). In addition, since SULT2A1 catalyzes the sulfonation of toxic monohydroxy bile acids (Kitada et al, 2003), its continuous expression during fetal and postnatal life may be essential to avoid bile acid stress and the emergence of intrahepatic cholestasis, a life-threatening event in the developing human (Howard and Murphy, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy pregnant women have higher total BA levels than non-pregnant women and levels up to 11.0 μmol/l are considered as normal in late gestation [40]. In ICP, abnormal BA profiles have been found in maternal serum, fetal circulation and meconium [41] and serum BA composition in women with ICP generally shows a shift towards a hydrophobic pattern, with higher levels of lithocolic acid and free bile acids [42]. Glantz et al showed that the probability of fetal complications increased by 1 -2% per additional μmol of maternal BA [1].…”
Section: Symptoms and Diagnosismentioning
confidence: 99%